Voices of militant women herstories or revolutionaries of the first quarter storm of 1970 - Cupino, Fleur de Lys C. (2006)
Voices of Militant Women (herstories of Revolutionaries from the First Quarter Storm of 1970) documents the life stories of seven women revolutionaries who valiantly fought the Marcos dictatorship. 35 years after the FQS, these women are still involved in the struggle for social transformation and women emancipation. This work is a contribution to women historiography, adding to the dearth of literature on contemporary women revolutionaries. It is a contribution to making women visible in history and in engendering history. It gives space to women's voices, unearthing their narratives from the margins of historical discourse. This is an attempt to document the living, for women need not die first to be recorded and remembered. The objective of the thesis is to have an insight into the personal lives of women revolutionaries from the FQS period, particularly on their early life experiences, relationship with parents, husbands (if any), children (if any) and friends, as well as how they are today, 35 years after the FQS. The resource persons came from the student movement of the general period of the FQS who joined the national democratic movement as full time revolutionaries. The thesis did not cover the other revolutionaries of the period who belonged to different ideological and political persuasions nor of the unaffiliated nationalists or activists. All of the resource persons did organizing and other work in the countrysides and/or in the urban areas. All except one studied at the University of the Philippines in Diliman, Quezon City. However, they did not become revolutionaries all the same time. Their experiences are varied as they are rich. Five of the women are no longer connected with the national democratic movement. All of them learned a lot form their involvement in the struggle and in the movement. But they have evolved a new life with new political and/or organizational commitments. All the seven women are currently engaged in the legal arena in the movement for change. The methodology used was participatory, consistent with feminist research. Women were able to tell their stories on their own terms, using their own voice and style. They edited and finalized their stories. However, due to limitations of time, the research design did not permit that the conceptual framework and methodology be consulted with the resource persons. The data construction, findings, analysis, conclusions and recommendations are entirely my own, and my resource persons may not agree on my own reading of their stories. the stories are about the revolutionary women's journey in life, the contradictions and dilemmas they faced, and the stimuli that contributed to becoming the persons and the women that they are today. Let us hear their voices.....
"March 2006."
Thesis (M.A.Women and Development)--University of the Philippines Diliman.
Keywords: Women revolutionaries -- History -- 20th century. -- Philippines; Women political activists -- History -- 20th century. -- Philippines; Philippines -- Politics and government